Managing high potential employees: a case of employers in Malaysia - Juhdi, Nurita (2013)
The main objective of the survey was to determine high potential (HIPO) employee development practices in Malaysia. Two hundred and thirty seven establishments from various industries participated in the survey. They were from diverse industries such as automotive, education, plantation, banking, financial services and insurance. The findings indicated that employers put highest emphasis on employees who were customer service oriented and able to create high performing teams. In terms of methods used to identify HIPOs in organizations, the most common method was performance appraisal by the immediate superior and the least common method was nomination method. Two most common methods to develop HIPOs were job enlargement and executive development programs and the least used was executive MBA program.